2019
DOI: 10.1111/ahe.12442
|View full text |Cite
|
Sign up to set email alerts
|

The spleen morphophysiology of fruit bats

Abstract: Spleen is one of the important lymphoid organs with wide variations of morphological and physiological functions according to species. Morphology and function of the spleen in bats, which are hosts to several viral strains without exhibiting clinical symptoms, remain to be fully elucidated. This study aims to examine the spleen morphology of fruit bats associated with their physiological functions. Spleen histological observations were performed in three fruit bats species: Cynopterus titthaecheilus (n = 9), R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 84 publications
(109 reference statements)
3
11
0
Order By: Relevance
“…The presence of PELS‐like structure is thought to be an additional mechanical barrier structure of fruit bats' spleen that is not shared by other species of mammals in general. These findings support the primary function of fruit bats spleen as blood pathogen filtration organs (Hanadhita et al, ). A further study to identify the phenotype of the associate cells around reticular ring would be needed to ascertain the PELS structure and its function in fruit bats.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…The presence of PELS‐like structure is thought to be an additional mechanical barrier structure of fruit bats' spleen that is not shared by other species of mammals in general. These findings support the primary function of fruit bats spleen as blood pathogen filtration organs (Hanadhita et al, ). A further study to identify the phenotype of the associate cells around reticular ring would be needed to ascertain the PELS structure and its function in fruit bats.…”
Section: Discussionsupporting
confidence: 84%
“…Visualization of the reticular meshwork can better demonstrate some splenic compartments. Hanadhita et al () described the presence of vascular space in the spleen of the fruit bats and have not yet been able to ascertain whether the structure is sinuses or venules. In this study, vascular space was identified as being limited by reticular fibres.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations